Surviving in the trails: teacher’s lived experiences in remote areas - Galut, Mark Neil A. (Frontiers in Sociology, 2025)
This study examines the experiences of teachers who are assigned to teach in remote areas. This qualitative hermeneutic phenomenological research study investigates the teachers’ journeys in surviving the trails of teaching in remote areas. Using hermeneutic phenomenological research methods, such as in-depth interviews and focus group discussions, this study found that assigning teachers to remote areas or distant locations is difficult not only in Kabugao District but also across the country. The findings revealed that surviving in the trails of the lived experiences of teachers in a remote areas had diverse experiences: Accessibility at the end of the trail, teachers’ love and passion, experience is the best teacher, eagerness behind challenges, culture-based teaching, teaching is fulfilling a life-changing experience, quality education is possible through support and connection, twenty-first-century teachers and twenty-first-century IP learners in remote area. Going to their respective stations needs to hike for almost a day or ride on a boat for almost 5 h. Teachers sacrifice their own money for the welfare of their learners. They provide a valuable contribution to our understanding of the challenges and resilience of teachers working in remote areas. Teachers of this study suggest increasing the support for the next teachers who are assigned to teach in remote areas and include the provision of adequate resources and infrastructure, as well as the development of support networks to improve their working conditions.